2007
DOI: 10.1063/1.2712821
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cobalt population on the structural properties of CoxFe3−xO4

Abstract: Co x Fe 3 − x O 4 -based (x=0.05–1.6) nanoparticles prepared by combustion reaction were investigated using x-ray diffraction, Raman spectroscopy, and Mössbauer spectroscopy. The Mössbauer data revealed Co2+ in both tetrahedral (site A) and octahedral (site B) sites of the cubic ferrite structure. For x⩽0.4 the experimental data indicated the synthesis of a core-shell structure, with hematite as the shell and cobalt ferrite as the core of the nanoparticle. Differences in crystalline structure between the two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 8 publications
5
32
0
4
Order By: Relevance
“…In addition, the appearance of the weakly magnetic, impure phase of α-Fe 2 O 3 (shown in Figure 2(c)) can reduce the saturation magnetization [18]. Also, the cation site occupancy in CoFe 2 O 4 nanoparticles is different than in the bulk [43]. In fact, since the nanoparticles are the mixed spinel structure type rather than the inverse spinel structure type (bulk) because of the presence of Co 3+ ions and also a cation distribution with cobalt ions on the tetrahedral site [44], the saturation magnetization is reduced [45].…”
Section: Phase Composition and Morphology Of Precursors Andmentioning
confidence: 99%
“…In addition, the appearance of the weakly magnetic, impure phase of α-Fe 2 O 3 (shown in Figure 2(c)) can reduce the saturation magnetization [18]. Also, the cation site occupancy in CoFe 2 O 4 nanoparticles is different than in the bulk [43]. In fact, since the nanoparticles are the mixed spinel structure type rather than the inverse spinel structure type (bulk) because of the presence of Co 3+ ions and also a cation distribution with cobalt ions on the tetrahedral site [44], the saturation magnetization is reduced [45].…”
Section: Phase Composition and Morphology Of Precursors Andmentioning
confidence: 99%
“…[13] it is shown that cobalt ferrite particles obtained by precipitation from an aqueous solution can crystallize in the normal spinel form, whilst in Ref. [14] it is reported that cobalt ferrite has mixed spinel structure (both normal and inverse spinel).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, both Raman modes at 612 and 682 cm -1 are reflecting the local lattice effect in the tetrahedral sublattice, while the peak at 468 cm -1 is probing the local lattice effect in the octahedral sublattice. 39,40 The same Raman bands mentioned above as well as additional bands at 222 cm -1 and 286 cm -1 can be seen in samples ZC31/4 to ZC11/8; these additional bands can be assigned to α-Fe 2 O 3 , which has very intense bands at these positions, shown in the Figure 3 for convenience. The Raman data thus confirm the observed significant difference between sample ZC13/8 and samples ZC31/4 to ZC11/8 by Mossbauer spectroscopy, i.e.…”
Section: 2 Phase Composition and Crystal Structure Of Ternary MIXmentioning
confidence: 71%